Cognitive predictors of understanding treatment decisions in patients with newly diagnosed brain metastasis. Issue 12 (3rd March 2015) - Gerstenecker, Adam; Meneses, Karen; Duff, Kevin; Fiveash, John B.; Marson, Daniel C.; Triebel, Kristen L.
<x xml:space="preserve">Abstract</x> BACKGROUND Medical decision‐making capacity is a higher‐order functional skill that refers to a patient's ability to make informed, sound decisions related to care and treatment. In a medical context, understanding is the most cognitively demanding consent standard and refers to a patient's ability to comprehend information to the extent that informed decisions can be made. METHODS The association between reasoning and cognition was examined using data from 41 patients with diagnosed brain metastasis. All diagnoses were made by a board‐certified radiation oncologist and were verified histologically. In total, 41 demographically matched, cognitively healthy controls were also included to aid in classifying patients with brain metastasis according to reasoning status (ie, intact or impaired). RESULTS Results indicate that measures of simple attention, verbal fluency, verbal memory, processing speed, and executive functioning were all associated with understanding, and that verbal memory and phonemic fluency were the primary cognitive predictors. Using these two primary predictors, equations can be constructed to predict the ability to understand treatment decisions in patients with brain metastasis. CONCLUSIONS Although preliminary, these data demonstrate how cognitive measures can estimate understanding as it relates to medical decision‐making capacities in these patients. Clinically, these findings suggest that poor verbal memory and expressive language function could serve as "red flags" for reduced consent capacity in this patient population, thus signaling that a more comprehensive medical decision‐making capacity evaluation is warranted. Cancer 2015;121:2013–2019. © 2015 American Cancer Society.